Public Sector Size and Performance Management : A Case Study of Post-Revolution Tunisia - Brockmeyer, Anne (World Bank Group, Washington, DC, 2015)
This paper examines public sector size and performance management in post-revolution Tunisia, drawing on macro-empirical, legal, and qualitative analyses. The paper first shows that public sector employment figures and the wage bill have increased significantly since the 2011 revolution, but that this represents merely an acceleration of the previous trend. The paper then examines de jure and de facto performance management in Tunisia's public sector, covering incentives through recruitment, evaluation, compensation, and promotion. The examination shows that Tunisia's legal framework is well-designed for recruiting the most skilled candidates into the public sector and promoting the most high-performing employees. De facto, the link between an employee's performance and evaluation, compensation, and promotion is weak. Performance evaluation is virtually nonexistent and promotions are automatic or awarded through a process that emphasizes seniority over performance. This is particularly true during the post-revolution period, in which a number of ad-hoc arrangements multiplied divergences between the legal basis for performance management and its application. These ad-hoc changes allowed the state to act as employer of last resort, significantly increasing direct (noncompetitive) recruitment and regularizing temporary staff. The increase in and proliferation of allowances have added to the complexity of the compensation system. In a qualitative review of past reform attempts, the paper demonstrates that reformers had identified the weaknesses of Tunisia's public sector performance system as early as 1989, but failed to achieve major change.